Effect of heat-treatment and reinforcement with silicon carbide on the microstructure and mechanical properties of alfevsi alloy - Arhami, M.; Sarioglu, Filiz; Kalkanli, Ali (American Society of Mechanical Engineers (ASME) infocentral@asme.org, 2007)
The aging response of Al-Fe-V-Si composite was compared with the un-reinforced alloy. The effects of solutionizing time, alloying element and SiC reinforcement on the age hardening response, microstructure and mechanical properties of these alloy and its composites was also investigated. The study was performed by T6 heat treatment at three different solutionizing times. Room temperature tensile testing was conducted for peak aged specimens to determine the effect of this heat treatment on the strength of squeezed cast un-reinforced and reinforced Al-Fe-V-Si alloy with SiC particles. The presence of SiC particles accelerated the aging kinetics of the composites compared to the unreinforced alloys. The time to reach peak age hardness was decreased by addition of SiCp. Mainly two different Fe-intermetallics; small ?-Al7(Fe,V)3Si and large?-Al18Fe11Si phases were present in the system studied. The fracture surfaces of composites revealed decohesion of SiC particles from the matrix and cracking of needle like-? intermetallics was observed. © © 2007 ASME & The Boeing Company.
ASME 2007 International Mechanical Engineering Congress and Exposition, IMECE 2007 -- 2007-11-11 through 2007-11-15 -- Seattle -- 112020
Keywords: Age hardening; Alloying elements; Alloys; Aluminum; Heat treatment; Intermetallics; Iron alloys; Mechanical properties; Microstructure; Reinforcement; Silicon; Silicon alloys; Silicon carbide; Tensile strength; Tensile testing; Effect of heat treatments; Fe intermetallics; Fracture surfaces; Hardening response; Microstructure and mechanical properties; SiC reinforcement; T6 heat treatment; Unreinforced alloys; Vanadium alloys